دور الاتصال الشخصي في تعزيز ولاء الزبون دراسة ميدانية على عينة من الباعة الصيدلانيين ببلدية سدراتة ولاية سوق أهراس - بوراس أبراهيم; مومني عبد النور (My University, 2025)
Abstract: This study seeks to examine the role of personal communication in fostering customer loyalty, by conducting a field investigation involving a sample of pharmaceutical salespersons in the municipality of Sedrata, located in the province of Souk Ahras. The central research question posed is as follows:  To what extent does personal communication contribute to enhancing customer loyalty among pharmaceutical salespersons? The study adopts a descriptive approach, utilising the survey method. A structured questionnaire was employed as the primary instrument for data collection, supplemented by direct observation. A comprehensive survey was carried out, encompassing the entire study population, which comprised 20 pharmacies within the municipality of Sedrata. The research yielded a number of significant findings, most notably:  Personal communication constitutes a key determinant in strengthening customer loyalty to pharmacies.  Effective listening and positive interpersonal engagement by salespersons play a pivotal role in building trust and reinforcing customer loyalty.  Non-verbal communication—such as eye contact, smiling, and gestures—enhances the overall customer experience and contributes to greater loyalty.  Variations in communication competencies among pharmaceutical salespersons result in differing levels of customer loyalty across pharmacies.  Ongoing personal interaction between the salesperson and customers helps to cultivate emotional bonds, which in turn manifest as repeated visits and recommendations of the pharmacy to others.  A statistically significant relationship was identified between the level of personal communication and the degree of customer loyalty. ------------------------------- ملخص الدراسة: تهدف هذه الدراسة للتعرف على دور الاتصال الشخصي في تعزيز ولاء الزبون، من خلال اجراء دراسة ميدانية على عينة من الباعة الصيدلانيين ببلدية سدراتة ولاية سوق اهراس، محاولين الإجابة على التساؤل المركزي الآتي:  ما هو دور الاتصال الشخصي في تعزيز ولاء الزبون لدى الباعة الصيدلانيين؟ فهي عبارة عن دراسة وصفية اعتمدنا فيها على المنهج المسحي حيث استخدمنا الاستمارة كأداة رئيسية لجمع البيانات، بالإضافة للملاحظة، وقمنا بمسح شامل لمجتمع الدراسة والمتكون من 20 صيدلية على مستوى بلدية سدراتة، وانتهت الدراسة بمجموعة من النتائج أبرزها:  الاتصال الشخصي يمثل عاملا اساسيا في تعزيز ولا الزبون للصيدلية.  جودة الاستماع والتفاعل الايجابي من قبل الباعة تساهم في تعزيز ولاء الزبائن وزيادة ثقتهم.  الاتصال الغير اللفظي كالتواصل البصري والابتسامة والايماءات، يعزز تجربة الزبون ويزيد من ولائه.  الاختلاف في مهارات الاتصال بين الباعة الصيدلانيين يؤدي إلى تباين مستويات ولاء الزبائن بين صيدلية واخرى.  الاتصال الشخصي المستمر بين البائع والزبائن يعزز الروابط العاطفية مما يترجم تكرار الزيارات والتوصية بالصيدلية للآخرين.  هناك علاقة ذات دلالة احصائية بين مستوى الاتصال الشخصي ودرجه الولاء. ----------------------------- Résumé de l'étude : Cette étude vise à identifier le rôle de la communication interpersonnelle dans le renforcement de la fidélité du client, à travers une enquête de terrain menée auprès d’un échantillon de vendeurs pharmaceutiques dans la commune de Sedrata, wilaya de Souk Ahras. Nous avons tenté de répondre à la question centrale suivante : ➢ Quel est le rôle de la communication interpersonnelle dans le renforcement de la fidélité du client chez les vendeurs pharmaceutiques ? Il s'agit d'une étude descriptive basée sur la méthode de l’enquête, où nous avons utilisé le questionnaire comme principal outil de collecte des données, en plus de l'observation. Nous avons effectué un recensement exhaustif de la population d'étude composée de 20 pharmacies situées dans la commune de Sedrata. L'étude a abouti à plusieurs résultats, dont les plus importants sont : ➢ La communication interpersonnelle constitue un facteur fondamental dans le renforcement de la fidélité du client envers la pharmacie. ➢ La qualité d'écoute et l'interaction positive des vendeurs contribuent à renforcer la fidélité des clients et à accroître leur confiance. ➢ La communication non verbale, telle que le contact visuel, le sourire et les gestes, améliore l’expérience client et augmente sa fidélité. ➢ La variation des compétences en communication entre les vendeurs pharmaceutiques entraîne des niveaux différents de fidélité d'une pharmacie à une autre. ➢ Une communication interpersonnelle continue entre le vendeur et les clients renforce les liens émotionnels, ce qui se traduit par des visites répétées et des recommandations de la pharmacie à d'autres personnes. ➢ Il existe une relation statistiquement significative entre le niveau de communication interpersonnelle et le degré de fidélité.
Keywords: الاتصال الشخصي، ولاء الزبون، الباعة الصيدلانيين، الصيدلية، جودة العلاقة